Cultivating global partnerships: Faculty of Pharmacy, UiTM Hosts Indonesian University delegations / Zakiah Mohd Noordin and Associate Prof. Dr. Mahmathi Karuppannan - Mohd Noordin, Zakiah; Karuppannan, Mahmathi (Faculty of Pharmacy, 2023)
Faculty of Pharmacy, UiTM, hosted esteemed delegates from Sekolah Tinggi Ilmu Kesihatan (STIKES), Keluarga Bunda Jambi, and Pakuan University, Indonesia, on July 12 and July 27, respectively. These visits mark a significant milestone in fostering global collaborations between UiTM and prominent higher education institutions in Indonesia. The visit commenced with a welcoming session by Dr. Mohd Shahezwan Abd. Wahab, Deputy Dean of Academic Affairs, and Dr. Norkasihan Ibrahim, Deputy Dean of Industry, Community, and Alumni Network. During this session, delegations led by Mdm. Silvia Mariana, Head of STIKES Keluarga Bunda Jambi and Dr. Asep Denih, Dean of the Faculty of Mathematics and Natural Science, Pakuan University, were introduced to the diverse range of academic programs, research expertise, and cutting-edge facilities available at the Faculty of Pharmacy, UiTM. Furthermore, reciprocal introductions were exchanged, affording both parties an opportunity to share insights about their respective institutions. This insightful exchange served as the bedrock for potential collaborative ventures. Productive discussions ensued, delving into potential areas of cooperation such as joint research initiatives, faculty and student exchanges, and participation in international conferences and innovation competitions. In addition, scheduled meetings were held among student representatives to initiate a community-based program that could nurture cross-cultural understanding and enrich the learning experiences of young minds.